2022
DOI: 10.3390/agriculture12071065
|View full text |Cite
|
Sign up to set email alerts
|

Recommending Advanced Deep Learning Models for Efficient Insect Pest Detection

Abstract: Insect pest management is one of the main ways to improve the crop yield and quality in agriculture and it can accurately and timely detect insect pests, which is of great significance to agricultural production. In the past, most insect pest detection tasks relied on the experience of agricutural experts, which is time-consuming, laborious and subjective. In rencent years, various intelligent methods have emerged for detection. This paper employs three frontier Deep Convolutional Neural Network (DCNN) models—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Based on our research, we found several studies comparing YOLOv5 to previous versions of YOLO, such as YOLOv4 or YOLOv3, as well as YOLOv5. According to a study provided by Li et al [ 21 ], YOLOv5 was more efficient and about 2.5 times faster. YOLOv3-AFF was compared to YOLOv3, and mAP was increased by 10.18% [ 22 ].…”
Section: Experimental Results and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our research, we found several studies comparing YOLOv5 to previous versions of YOLO, such as YOLOv4 or YOLOv3, as well as YOLOv5. According to a study provided by Li et al [ 21 ], YOLOv5 was more efficient and about 2.5 times faster. YOLOv3-AFF was compared to YOLOv3, and mAP was increased by 10.18% [ 22 ].…”
Section: Experimental Results and Analysesmentioning
confidence: 99%
“…In recent years, YOLO-based target detection algorithms have been successfully applied in pest detection. For instance, YOLOv5 was more efficient at detecting insect pests with higher accuracy and about 2.5 times faster when the background images were simple, such as the Baidu AI insect detection dataset [ 21 ]. To improve the accuracy of insect identification, the YOLOv3-AFF network with the adaptive feature fusion was employed to reuse features at various scales, and it achieved 72.10% accuracy on the Pest24 dataset [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers have used DL-based object-detection models to overcome the limitation of the CNN-based methods. For instance, Li et al [ 25 ] utilized the IPI02 dataset to detect insects in fields using various DCN networks, including Faster-RCNN, Mask-RCNN, and YOLOv5. They obtained promising results and demonstrated that YOLOv5 outperformed Faster-RCNN and Mask-RCNN, which attained 99% accuracy, whereas YOLOv5 gained 97%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A precision of 53.6% was reached in this investigation using the IP102 dataset. Li et al [42] implemented the Mask-RCNN ResNet50, Faster-RCNN ResNet101, and Yolov5 Darknet53 models for pest recognition. These methods each reached accuracy levels of 99.6%, 99.4%, and 97.6%.…”
Section: Literature Reviewmentioning
confidence: 99%